EVALUATE THE DIAGNOSIS OF NEONATAL SEPSIS BY MEASURING INTERLEUKINS: A SYSTEMATIC REVIEW - Ainun Rosydz, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Neonatal sepsis is a clinical condition that manifests within the first month of a newborn's life and is accompanied by systemic bacteremia. Early onset sepsis (EOS) and late onset sepsis (LOS) are the two categories that make up neonatal sepsis (LOS). The first hour of birth is when signs of early-onset sepsis appear in babies, and 90 percent of symptoms appear during the first 24 hours of life. We determined the levels of CRP, IL-6, IL-8, TNF-, and sCD163 in the serum of infected, non-infected, and control neonates prior to the administration of antibiotics, at 24 hours after the administration of antibiotics, and at 48 hours after the administration of antibiotics during the course of this study, which took place over the course of two years. Our findings add credibility to the use of early IL-6 testing as a technique for the quick detection of neonatal sepsis. This is particularly true in babies who were delivered to women who had risk factors. In a previous study, the level of IL-6 was not demonstrated to be predictive of neonatal sepsis in neonates who did not have any risk factors. This was the case even though the study was conducted in neonates who did have risk factors.